2022
DOI: 10.3389/fimmu.2022.894534
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Increase in Susceptibility and Severity of Secondary Bacterial Infections During SARS-CoV-2

Abstract: Secondary bacterial infections can exacerbate SARS-CoV-2 infection, but their prevalence and impact remain poorly understood. Here, we established that a mild to moderate infection with the SARS-CoV-2 USA-WA1/2020 strain increased the risk of pneumococcal (type 2 strain D39) coinfection in a time-dependent, but sex-independent, manner in the transgenic K18-hACE2 mouse model of COVID-19. Bacterial coinfection increased lethality when the bacteria was initiated at 5 or 7 d post-virus infection (pvi) but not at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 160 publications
0
7
0
Order By: Relevance
“…Thus, a substantial body of evidence beyond the current study also points towards COVID-19 coagulopathies being due to bacterial, and possibly adenoviral, infections complicating SARS-CoV-2 and activating synergistic sets of Toll-like receptors resulting in a hyperinflammation. This effect has been demonstrated for a combination of SARS-CoV-2 with Streptococci in mouse models of coinfection [ 129 , 130 ]. Notably, this hyperinflammatory state could be prevented by vaccination against either SARS-CoV-2 or pneumococci.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, a substantial body of evidence beyond the current study also points towards COVID-19 coagulopathies being due to bacterial, and possibly adenoviral, infections complicating SARS-CoV-2 and activating synergistic sets of Toll-like receptors resulting in a hyperinflammation. This effect has been demonstrated for a combination of SARS-CoV-2 with Streptococci in mouse models of coinfection [ 129 , 130 ]. Notably, this hyperinflammatory state could be prevented by vaccination against either SARS-CoV-2 or pneumococci.…”
Section: Discussionmentioning
confidence: 97%
“…Other implications of our data can be tested in animal models. For example, SARS-CoV-2-susceptible species (such as golden hamsters or some strains of mice) might be co-infected with the virus and with bacteria such as group A Streptococci, Staphylococci, Klebsiella, Acinetobacter or Haemophilus , or with viruses such as adenovirus type 5 (e.g., [ 129 , 130 ]). The effect of such bacterial coinfections on vaccination with SARS-CoV-2 vaccines could be tested in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…As presented in the study timeline (Figure 1A), mice were inoculated with PBS or infected with a low dose (500 PFU) of the A lineage strain, WA1. The dose was chosen to enable infection but allow at least two-thirds of the cohort to survive for the subsequent challenge reported previously [18]. Of the low-dose WA1-infected cohort, 44/64 (68.75%) survived infection (Figure 1B).…”
Section: A Low Dose Of Sars-cov-2 Confers Greater Protection In Homol...mentioning
confidence: 96%
“…Early during the COVID-19 pandemic, Di Stadio et al [32] argued that the nasal microbiome was important for immunomodulatory protection against the COVID-19 infection. Smith et al [33] and Jochems et al [34] reported that carriage of specific nasal bacteria was important in the host response and resistance/vulnerability to COVID-19 infection. Specific nasal bacteria were directly connected with specific cytokine production and, thereby, affected whether airway-damaging mucosal inflammation occurred during the response to COVID-19.…”
Section: Microbiota and Risk Of Viral And/or Bacterial Pathogenesismentioning
confidence: 99%
“…Considering that it is (1) more than a century since an influenza pandemic produced high levels of death by bacterial pneumonia, and (2) we know that prominent animal respiratory coronaviruses often produce death via bacterial pneumonia, it is not surprising that bacterial and/or fungal infections increased COVID-19 case severity and often resulted in death [47]. Using the K18-hACE2 mouse model of COVID-19, Smith et al [33] performed a study examining the time-sensitive immunological mechanisms through which the SARS-CoV-2 virus increases the susceptibility and pathogenicity of bacterial co-infection. Immunologically, Peng et al [48] found that coronavirus impairs the host's ability to clear bacterial pathogens by interfering with lysosomal function.…”
Section: The Covid-19 Example With Bacterial And/or Fungal Infections...mentioning
confidence: 99%